EFEITO DA SUPLEMENTAÇÃO DO ÓLEO DA SEMENTE DE UVA (VITIS VINIFERA L.) E DO ÓLEO DE SEMENTE DE LINHAÇA (LINUM USITATISSIMUM) EM CAMUNDONGO SWISS - CAROLINA DI PIETRO FERNANDES (2024)
Vegetable oils extracted from seeds, grains and fruits are extremely important for human nutrition and the industrial sector. Thus, mono- and polyunsaturated fatty acids and the bioactive substances presented have beneficial effects on health and are used for the development of cosmetics, pharmaceutical products and foods. Thus, grape seed oil (G), linseed oil (L) and the Mixture (GL), composed of grape seed oil and linseed oil in the same volume 1:1 (v/v), can present quality and stability, in addition to having positive effects in an in vivo experimental model. Given this, we evaluate the oils, physical-chemical analyses, oxidative stability: Rancimat, thermal analyzes such as thermogravimetry/derivative thermogravimetry (TG/DTG) and differential scanning calorimetry (DSC), optical analyzes of UV-Vis absorption and emission matrix- fluorescence stimulation, total carotenoids and color, in addition to assessments of consumption, weight behavior, biochemical and histological parameters in an in vivo experimental test. The fatty acid profile showed a higher fraction of linoleic acid (C18:2) in G (52.40 ± 1.34) and GL (42.53 ± 0.2) and a higher fraction of alpha-linolenic acid (C18:3). in L (53.30 ± 0.03). The quality and identity indexes are within the recommended ranges for all samples tested, the acidity value was higher in L (2.8 mg KOH/g) and the peroxide index was higher in G (6.5 mEqO2/kg ). ). The values of the refractive indices, iodine (Wijs), saponification and relative density support that the oils are suitable for consumption. TG/DTG, DSC and rancimat analyzes behaved similarly. Optical analyzes revealed a higher carotenoid content in L (13.67 ± 1.74) and GL (6.23 ± 0.54) compared to G (1.16 ± 0.15), highlighting congruence in the analysis results by heart. In the in vivo test, group G, at a dosage of 2,000mg/kg/day (G2) promoted lower consumption (p